Gastrointestinal Complications of Diabetes A Comprehensive Guide (Clinical Gastroenterology, 2018)
This text provides a state-of-the art review of the gastrointestinal complications of diabetes, their pathophysiology, clinical manifestations, diagnostic evaluation and management. Divided into six sections, the volume shows how diabetes affects the entire GI tract, from the oral cavity and esophagus to the large bowel and anorectal region. By offering a detailed diagnostic approach and featuring therapeutic algorithms at the end of each chapter, the text is a useful guideline and reference point for every day practice, specifically in recognizing and diagnosing patients with gastrointestinal complications of diabetes in a timely fashion. Written by experts in the field, Gastrointestinal Complications of Diabetes: A Comprehensive Guide is a valuable resource for physicians dealing with diabetes mellitus or gastrointestinal disorders, and researchers interested in this multidisciplinary problem. .